Carbon "peapods" - a new tunable nanoscale graphitic structure (Review Article): - Krive, Ilya V.; Shekhter, Robert I.; Jonson, Mats (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
We consider the ectronic properties of empty single-wall nanotubes (SWNT) and SWNT filled with the fullerenle molecules (carbon «nano-peapod»). The first part of the review (section 2) is devoted mostly to the Luttinger liqued properties of individual metallic SWNT coupled to metallic electrodes or to superconducting leads. The discovery of carbon «nano-peapods» and their elastic, electric and thermal properties are reviewed in the second part of the paper (section 3). We suggest in particularly how fullerene and metallofullerene molecules can be raleased from a «nano-peapod» by a purely electrostatic method.